2019
DOI: 10.1002/lary.28454
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm shift in surgery for benign parotid tumors: 19 years of experience with almost 3000 cases

Abstract: Objectives The aim of this study was to explore the changes in philosophy in the surgical therapy of benign parotid tumors over a period of 19 years. Methods The records of all patients treated for benign parotid tumors between 2000 and 2018 were evaluated. Data were analyzed with respect to the number of procedures carried out per year of the study according to each of the different surgical modalities and the incidence of postoperative complications. Statistical analysis was performed using the x2 test. A P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
3
12
0
2
Order By: Relevance
“…22,76 Therefore, based on the results of the current study and previous reports, enucleation should not be considered in the management of benign parotid tumors. 5 The higher recurrence rate associated with enucleation could be attributed to that some benign parotid tumors, particularly pleomorphic adenoma, can produce pseudopods extending outside the tumor capsule which might be left behind in the surgical bed during tumor resection. 75 It is also important to note that long follow-up is required for an optimum evaluation of tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,76 Therefore, based on the results of the current study and previous reports, enucleation should not be considered in the management of benign parotid tumors. 5 The higher recurrence rate associated with enucleation could be attributed to that some benign parotid tumors, particularly pleomorphic adenoma, can produce pseudopods extending outside the tumor capsule which might be left behind in the surgical bed during tumor resection. 75 It is also important to note that long follow-up is required for an optimum evaluation of tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, tumor recurrence, facial nerve paralysis, and other complications (Frey's syndrome [FS], sialocele, and salivary fistula) continue to be reported following all the above‐mentioned surgical interventions 5,19–20 …”
Section: Introductionmentioning
confidence: 99%
“…In ECD, the facial nerve is not identified intentionally, and unlike enucleation, the lesion is removed outside of the capsule. Bär et al 20 examined approximately 3,000 surgeries performed in 2000 to 2018 and reported a rapid increase in ECD in this decade. Furthermore, many reports consistently demonstrate that the rate of postoperative facial nerve palsy and Frey syndrome is lower for ECD than for PSP 21 because ECD is indicated for small tumors located superficially.…”
Section: Discussionmentioning
confidence: 99%
“…tomischen Kapseldefektes stellt auch die Grundlage der Philosophie der sogenannten extrakapsulären Dissektion dar. Bei dieser Operationsmethode besteht die Aufgabe des Operateurs darin, in der Präparation möglichst außerhalb der Tumorkapsel ("extrakapsuläre Dissektion") des PA zu bleiben, um die Abdeckung eines potenziellen anatomischen Defektes von gesundem Gewebe sicherzustellen und den Tumor "im Gesunden" zu entfernen [17].…”
Section: Diskussionunclassified
“…Ebenso fiel die Rate der mikroskopischen fokalen Kapseldefekte (2,9 %) im Vergleich zur Literatur (14,3 [8] -20,1 % [5]) niedriger aus. Dies ist insofern von Relevanz, als dass die vermehrte Durchführung der "kapselnäheren Dissektion" (in Form der extrakapsulären Dissektion) im Vergleich zur konventionellen Parotischirurgie [17,20] nicht mit einer signifikant höheren Gefährdung der Adenomkapsel verbunden war. Die homogene Verteilung der 37 Fälle über die 16 Jahre der Studie (▶ Abb.…”
Section: Diskussionunclassified